Pengaruh Jumlah Kunjungan Wisatawan Dan Pajak Restoran Terhadap Pertumbuhan Ekonomi Kabupaten Tapanuli Utara Dengan PAD Sebagai Variabel Intervening - Abdi Sugiarto; Simon Patar Rizki Manalu; Evalina Pakpahan (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
Economic growth is one of the indicators used to see the level of success of the development of a region. Original Local Government Revenue is a source of regional revenue that will be used to develop the region. Support from the tourism sector is expected to have an influence on North Tapanuli's economic growth. To determine the effect, it is studied using existing data. The results of the study directly show that the number of tourist visits has a negative and insignificant effect on Original Local Government Revenue. Directly the number of tourist visits has a negative but not significant effect on regional economic growth. Directly restaurant tax has a positive but not significant effect on Original Local Government Revenue. Restaurant tax directly has a positive but not significant effect on regional economic growth. And directly Regional Original Income has a negative and insignificant effect on regional economic growth. Then, indirectly, Original Local Government Revenue is not significant to mediate the relationship between the number of tourist visits and regional economic growth through Original Local Government Revenue. Furthermore, indirectly PAD is not significant to mediate the relationship between restaurant tax and regional economic growth through Original Local Government Revenue.